Metal oxide-based photocatalysis : fundamentals and prospects for application - Zaleska-Medynska, Adriana (Metal oxides series., 2018)
Metal Oxide-Based Photocatalysis: Fundamentals and Prospects for Application explains the principles and fundamentals of metal oxide-based photocatalysis and the requirements necessary for their use in photocatalysis. It also discusses preparation methods for photocatalysis, and the advantages, disadvantages and achievements of the most important metal oxides (TiO2, ZnO, Fe2O3, Ta2O3, CuO, NiO, Cr2O3, RuO2, etc.). The book concludes with the most important photocatalytic applications and an overview of the future. Applications are organized by potential needs and solutions, addressing such areas as water treatment, hydrogen production, air treatment, chemical synthesis, and applications in medicine and construction.